MATH SOLVE

8 months ago

Q:
# witch of the following expression is equivalent to the logarithmic expression below. log(3)5/x^2A)log(3) 5+2 log(3)xB)log(3) 5-2 log(3)xC)2 log(3) 5-log(3)xD)log(3) 5+log(3)x

Accepted Solution

A:

assuing you mean

[tex]log_{3}(\frac{5}{x^2})[/tex]

remember that [tex]log(\frac{a}{b})=log(a)-log(b)[/tex]

also, [tex]log(x^m)=(m)log(x)[/tex]

so

[tex]log_{3}(\frac{5}{x^2})=[/tex]

[tex]log_{3}(5)-log_{3}(x^2)=[/tex]

[tex]log_{3}(5)-2log{3}(x)[/tex]

the answer is B

[tex]log_{3}(\frac{5}{x^2})[/tex]

remember that [tex]log(\frac{a}{b})=log(a)-log(b)[/tex]

also, [tex]log(x^m)=(m)log(x)[/tex]

so

[tex]log_{3}(\frac{5}{x^2})=[/tex]

[tex]log_{3}(5)-log_{3}(x^2)=[/tex]

[tex]log_{3}(5)-2log{3}(x)[/tex]

the answer is B